Alcohol consumption and reproductive health risks in rural Central Kenya - Muturi, Nancy W. (My University, 2014)
Objective: The goal of the current study is to explore the perceived reproductive health risks associated with alcoholism from the perspective of rural communities in Kenya where abuse of illicit liquor especially among men has become an epidemic. Methods: Data for the study were gathered qualitatively through focus groups among community members and in-depth interviews with opinion leaders and key informants who were selected through a snowball method. All recorded data were analyzed through constructivist and interpretive techniques, which started with a line-by-line examination of transcripts for identification of emerging themes. Results: Rural communities are aware of the lethal nature of the illicit liquor and the severe reproductive health problems associated with it among male consumers. Alcoholism also affects women’s sexual and reproductive needs and is attributed to risky sexual behaviors in alcohol-discordant relationships, which puts them at a higher risk of HIV infection. Conclusions: Results indicate a need to address alcoholism in rural Kenya as a public health problem focusing on education and understanding of the long-term health consequences. Addressing the impact on male reproductive health is crucial because it impacts the wider community. Given the complex relationship between alcohol abuse and HIV/AIDS, it is also important for prevention interventions to target married women and non-alcohol consumers. Furthermore, engaging communities will ensure development of culture- and gender-specific interventions. Such engagement requires facilitation of health practitioners for development of meaningful community-based initiatives.
Keywords: Alcohol consumption; Central Kenya; Reproductive health; Alcoholism; Alcohol abuse